Increased Body Mass Index & Waist Circumference are Associated with Female Infertility: A Cross-Sectional Study (Eastern Medical College Journal, 2023)
Background: The prevalence of obesity and overweight are increasing and has become an epidemic worldwide. Obesity has detrimental influences on all systems, including reproductive health. Obesity can lead to menstrual disturbance, anovulation, miscarriage, pregnancy complications and subfecundity and infertility. This study aimed to investigate the effects of body mass index (BMI) and waist circumference (WC) on infertility in women of childbearing age.Methodology: This was a hospital based cross-sectional observational study comprising hundred (100) infertile women aging 18-35 years in Outpatient Department of Obstetrics & Gynaecology and Endocrinology in Chittagong Medical College Hospital and Department of Biochemistry, Chittagong Medical College, Chattogram. Samples were taken by non-probability consecutive sampling. Important variables in this study were age, BMI, waist circumference and Blood Pressure.Results: Most of the infertile women were 21-30 years. In the study, among the infertile women increased BMI was found in 50% cases and increased waist circumference was found in 76% cases.Conclusion: Overweight and obese patients should be informed about the importance of pre-pregnancy weight reduction and should be encouraged to lose weight before the treatment to reduce the poor obstetrical outcomes due to obesity.Eastern Med Coll J. July 2023; 8 (2):39-42